Сказки - Салтыков-Щедрин Михаил Евграфович (Школьная библиотека для нерусских школ, 1989)
Экземпляры: ф. 2 (2001) / Инвентарный номер: 70751 / Цена: 21.60 / Авт.знак: С 16 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1